SARS-CoV2 infection: functional and morphological cardiopulmonary changes in elite handball players - Fikenzer, S.; Kogel, A.; Pietsch, C.; Lavall, D.; Stöbe, S.; Rudolph, U.; Laufs, U.; Hepp, P.; Hagendorff, A. (Scientific Reports, 2021)
There is increasing evidence of cardiac involvement post-SARS-CoV-2 infections in symptomatic as well as in oligo- and asymptomatic athletes. This study aimed to characterize the possible early effects of SARS-CoV-2 infections on myocardial morphology and cardiopulmonary function in athletes. Eight male elite handball players (27 ± 3.5 y) with past SARS-CoV-2 infection were compared with four uninfected teammates (22 ± 2.6 y). Infected athletes were examined 19 ± 7 days after the first positive PCR test. Echocardiographic assessment of the global longitudinal strain under resting conditions was not significantly changed (- 17.7% vs. - 18.1%). However, magnetic resonance imaging showed minor signs of acute inflammation/oedema in all infected athletes (T2-mapping: + 4.1 ms, p = 0.034) without reaching the Lake-Louis criteria. Spiroergometric analysis showed a significant reduction in VO2max (- 292 ml/min, - 7.0%), oxygen pulse (- 2.4 ml/beat, - 10.4%), and respiratory minute volume (VE) (- 18.9 l/min, - 13.8%) in athletes with a history of SARS-CoV2 infection (p < 0.05, respectively). The parameters were unchanged in the uninfected teammates. SARS-CoV2 infection caused impairment of cardiopulmonary performance during physical effort in elite athletes. It seems reasonable to screen athletes after SARS-CoV2 infection with spiroergometry to identify performance limitations and to guide the return to competition.